2019
DOI: 10.1093/mnras/stz900
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of young protoclusters embedded in dense massive clumps. A new grid of population synthesis SED models and a new set of L/M evolutionary tracks

Abstract: A grid of 20 millions 3-1100µm SED models is presented for synthetic young clusters embedded in dense clumps. The models depend on four primary parameters: the clump mass M clump and dust temperature T dust , the fraction of mass f core locked in dense cores, and the age of the clump t SF . We populate the YSO clusters using the Kroupa (2001) IMF and the YSOs SED models grid of Robitaille et al. (2006).We conduct extensive testing of SED fitting using a simulated dataset and we find that M clump essentially de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
5
12
0
Order By: Relevance
“…Sridharan et al (2002) found that the distance-independent ratio M/L of UCHii regions is lower (∼0.005) than the ratio of HMPOs (∼0.025), as UCHii regions are more evolved and thus more luminous. This has also been confirmed by observations of large samples of HMSFRs, e.g., by Molinari et al (2008Molinari et al ( , 2010; Maud et al (2015); Molinari et al (2016); Urquhart et al (2018); Molinari et al (2019). In Fig.…”
Section: Physical Structure Of High-mass Star-forming Coressupporting
confidence: 78%
“…Sridharan et al (2002) found that the distance-independent ratio M/L of UCHii regions is lower (∼0.005) than the ratio of HMPOs (∼0.025), as UCHii regions are more evolved and thus more luminous. This has also been confirmed by observations of large samples of HMSFRs, e.g., by Molinari et al (2008Molinari et al ( , 2010; Maud et al (2015); Molinari et al (2016); Urquhart et al (2018); Molinari et al (2019). In Fig.…”
Section: Physical Structure Of High-mass Star-forming Coressupporting
confidence: 78%
“…In highly obscured regions of galaxies dust completely blocks the light from stars within these regions. In particular young stars in compact star forming clouds are only visible through the dust re-emitted stellar photons (Molinari et al 2019). On large galactic scales, UV light from the plane of edge-on discs is also highly obscured by dust, and even optical images of edge-on galaxies exhibit strong dark lanes because of dust obstruction.…”
Section: ;mentioning
confidence: 99%
“…This is the ratio between the bolometric luminosity of clumps and their corresponding FWHM mass, a distance independent quantity. Previous works have shown that this ratio is a good indicator of evolutionary stage (Molinari et al 2008(Molinari et al , 2019, and so for the analysis within this study we shall use the L bol /M fwhm ratios of clumps to determine the global evolutionary phase of these star formation regions. The L bol /M fwhm ratios for the ATLASGAL sample range from 10 −2.4 to 10 3.3 L /M with a mean of 10 0.4 L /M .…”
Section: Temperatures and L Bol /M Fwhm Ratiosmentioning
confidence: 99%